LIFE SKILL AGAMA DI PONDOK PESANTREN DARUL AMANAH SUKOREJO KENDAL - Fatwa, M.; Khasan, Nur; Mukhrodi, Mukhrodi; Istinaroh, Istinaroh (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Islamic boarding schools as part of Indonesia’s Islamic educational heritage do not only focus on religious knowledge but also equip students with religious life skills to face contemporary challenges. A simple, independent, and worship-oriented lifestyle trains the santri to develop spiritual, moral, social, and practical skills that are useful in life. Through an integrated approach, pesantren are expected to produce a generation with good character, independence, and relevance to modern needs. This study aims to describe and analyze the implementation of religious life skills at Pondok Pesantren Darul Amanah Sukorejo Kendal. The type of research used is field research in the form of a qualitative study. Data collection was conducted using three methods: observation, interviews, and documentation. Religious life skills at Pondok Pesantren Darul Amanah Sukorejo Kendal are implemented systematically through programs such as Qur’an memorization (tahfidz), worship, morality (akhlak), public speaking (khitobah), and language, with direct practice embedded in daily activities. Routine evaluation is carried out through tests, observations, and performance assessments to measure students’ progress. Through this model, the pesantren has successfully shaped santri to be knowledgeable, virtuous, skillful, and ready to play a positive role in society in accordance with Islamic values. ABSTRAK Pesantren sebagai warisan pendidikan Islam di Indonesia tidak hanya berfokus pada ilmu agama, tetapi juga membekali santri dengan life skill agama agar siap menghadapi tantangan zaman. Kehidupan sederhana, mandiri, dan bernuansa ibadah melatih santri memiliki keterampilan spiritual, moral, sosial, serta praktis yang berguna dalam kehidupan. Dengan pendekatan terpadu, pesantren diharapkan mampu melahirkan generasi berakhlak, mandiri, dan relevan dengan kebutuhan modern. Penelitian ini bertujuan mendeskripsikan dan menganalisis implementasi life skill keagamaan di Pondok Pesantren Darul Amanah Sukorejo Kendal. Jenis penelitian ini adalah penelitian lapangan (field research) berbentuk kualitatif. Pengumpulan data menggunakan 3 metode yaitu observasi, wawancara, dan dokumentasi. Life skill agama di Pondok Pesantren Darul Amanah Sukorejo Kendal dilaksanakan secara terencana melalui program tahfidz, ibadah, akhlak, khitobah, dan bahasa dengan pembiasaan praktik langsung dalam keseharian. Evaluasi rutin dilakukan melalui tes, pengamatan, dan penilaian praktik untuk mengukur perkembangan santri. Dengan pola ini, pesantren berhasil membentuk santri berilmu, berakhlak, terampil, dan siap berperan positif di masyarakat sesuai nilai-nilai Islam.